(untitled) (Journal of the College of Basic Education, 2023)
Attitudes represent one of the concepts that psychologists follow in their attempts to identify the reality of what is going on inside that closed box that is called the human brain, which results in these different or repetitive forms and patterns of behavior (Al-Salami, BT, p. 154).Attitudes are among the main components of an individual’s personality, as they constitute a motivational component that directs and activates the individual’s behavior in situations that require him to respond with acceptance or rejection. It is assumed (Wade & Tavris 2005) that the attitude is the willingness to respond, meaning that the attitude is not the behavior, but rather a condition that precedes the behavior. (Anderson 2005) believes that the trend is what the individual expresses in consistent responses that have a degree of permanence and stability. Attitudes differ in the degree of their strength and weakness, and they are represented in a straight line, one of its sides representing acceptance and the other rejection (Abdullah, 2007, p. 57).Recognizing the attitudes of individuals in general is the basic step for developing them, confirming what is desirable, and setting plans to modify the unwanted ones, as the attitudes of individuals have a strong and decisive influence on their behavior and in directing others because they lead to the individual’s awareness and daily activities and affect the formation of his information, his interaction with others, and his feelings. Odeh, 1987, p. 52).